James Joyce, Irishness and the Exile Aesthetics: A Nationalistic Perspective - Zhang, Yi (Academia Journal of Humanities & Social Sciences, 2025)
This paper delves into the construction of nationality within the literary corpus of renowned Irish author James Joyce, examining it through the lens of exilic aesthetics. The study aims to elucidate the mechanisms by which he articulates the concept of Irishness. Through the meticulous textual analysis and critical discourse, the paper ascertains that he dismantles the colonially entrenched Irishness by challenging and resisting the colonial narrative of Ireland, and subsequently reconfigures this notion through an exilic sense of belonging, informed by an international modernist geographical imagination. This inquiry facilitates a reappraisal of the construct of "Irishness" within his oeuvre and its implications for Irish historical and cultural contexts. Furthermore, it incites contemplation on the role of intellectuals during the colonial epoch in shaping national identities and their engagement in both colonial defiance and the pursuit of national emancipation.